Anggaran Pada Umkm Jasa Episentrum Barbershop: Problematika Masa Kini - Syahbani, Ahmad Israq; Wulandari, Siti Athira; Normirawati, Normirawati; Mariani, Mariani; Irfan, Diandra Syahrani (Jurnal Ilmiah Akuntansi dan Keuangan, 2024)
The article discusses the financial profile, challenges, and budget management strategies at Episentrum Barbershop, founded in Makassar in 2013 by Zulkifli Alifwansa. Challenges include a lack of competent personnel in finance, intense industry competition, and income fluctuations. This research aims to identify the financial profile and devise strategies to address these challenges. The research method employed is a qualitative approach involving interviews and observations. Results show projected revenue and expenses for 2025, with discussions covering recommended budget management strategies to overcome challenges. In conclusion, Episentrum Barbershop has the potential to overcome challenges with the right strategies, but the article could be enhanced with a more engaging and detailed approach to the challenges faced.